Community-Based Cultural Tourism Potential In Karangturi Tourism Village, Lasem District, Rembang Regency - Sofiani Sofiani; Kevin Gustian Yulius; Gracia Eugene Hardjasa (Politeknik Internasional Bali, 2025)
Karangturi Tourism, Lasem District, Rembang Regency, which is famous for its acculturation of Javanese and Chinese cultures, as well as the heritage of Lasem batik which is a symbol of local cultural identity. Lasem, known as